Shape Optimization for Arch Dam with Sequential Quadratic Programming Method - Liu, Hui Bo; Duan, Yin; Yuan, Wei (Applied Mechanics and Materials, 2014)
The sequential quadratic programming method is introduced in arch dam shape optimization design. In the optimization computation, the arch dam volume is taken as objective function, and the calculation is realized by automatically considering loading process, equivalent stress computation and simulation of shape optimization for arch dam based on FEM. A parabola arch dam is used as a numerical example. The result shows that the optimized figure is much safer and more practical, which indicates that the SQP method is an effective way for optimization design of arch dam shape.